1994
DOI: 10.1093/geront/34.3.386
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Coping Among Caregivers of Spouses With Dementia

Abstract: Personality factors and coping strategies were examined among a sample of spouse caregivers. Fifty spouse caregivers of patients diagnosed with Alzheimer's disease or a related dementia completed the NEO-FFI, a personality inventory designed to measure traits identified in the five-factor trait model, and a revised measure of the Ways of Coping Checklist. Results from a series of multivariate regressions showed that personality traits explained 60% of the variance in emotion-focused coping, 30% of variance in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
153
3
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(181 citation statements)
references
References 0 publications
24
153
3
1
Order By: Relevance
“…They cited Hooker and Frazier (1994) This is somewhat contrary to the findings of , who in the study mentioned above found relationships not only with Neuroticism and coping, but also between Extraversion and coping, albeit with questions regarding causality. They found Extraversion to be related to rational action and thinking positively, among other things, and suggested "that the most pervasive and replicable factors in coping are closely related to the major personality dimensions of [Neuroticism] and [Extraversion]" (p. 394).…”
Section: Coping Styles and Personalitycontrasting
confidence: 64%
See 3 more Smart Citations
“…They cited Hooker and Frazier (1994) This is somewhat contrary to the findings of , who in the study mentioned above found relationships not only with Neuroticism and coping, but also between Extraversion and coping, albeit with questions regarding causality. They found Extraversion to be related to rational action and thinking positively, among other things, and suggested "that the most pervasive and replicable factors in coping are closely related to the major personality dimensions of [Neuroticism] and [Extraversion]" (p. 394).…”
Section: Coping Styles and Personalitycontrasting
confidence: 64%
“…Agreeableness to be related to seeking social support (Hooker & Frazier, 1994;O'Brien & DeLongis, 1996;Vickers et al, 1989), and cognitive restructuring and positive reappraisal (Connor-Smith & Flachsbart, 2007;Vickers et al, 1989). found a positive relationship between Agreeableness and problem-solving.…”
Section: Coping Styles and Personalitymentioning
confidence: 91%
See 2 more Smart Citations
“…Moreover Hooker et al [21] showed that extraversion was positively correlated with adaptive coping, especially problem-focused coping and seeking support. Neuroticism was related with emotion-focused coping but no relationship found between openness and coping strategies.…”
Section: Discussionmentioning
confidence: 99%